Evaluation of Knowledge Level of Zahedan Dental Students About Modern Prophylactic Antibiotic Regimens In Various Dental Treatments 2022-2023 - tahereh Nosratzehi; Abolfazl Payandeh; Ali Kamali (Babol University of Medical Sciences, 2023)
Background and Objective: Infective endocarditis is a rare condition that occurs in susceptible patients following invasive dental treatments. In order to prevent this complication, it is recommended to prescribe antibiotics for susceptible patients before performing some dental procedures. Therefore, the present study aims to survey the level of knowledge of students of the last three years of Zahedan Faculty of Dentistry about modern antibiotic prophylaxis regimens in various dental treatments was carried out in 2022. Methods: The current study is a cross-sectional observation (descriptive-analytical) and included 96 dental students of the last three years of Zahedan Medical Sciences in 2022. The data were collected using a questionnaire and entered into 24spss software for analysis. The chi-square test or Fisher's exact test was used to compare the frequency between groups (checking the assumption of independence).  Findings: According to the findings of the present study, 74% of the 96 people participating in the study had good knowledge about the new prophylactic antibiotic regimens in various dental treatments. In the final year of Zahedan dentistry, there was no statistically significant difference between women and men regarding modern antibiotic prophylaxis regimens (p=0.55). Also, there was a significant difference in the frequency of knowledge of Zahedan dentistry students in the last three years (p˂0.001). Conclusion: The results of the present study showed that the students had good knowledge about the new prophylactic antibiotic regimens in various dental treatments.